Meio ambiente e cooperativismo: vivências e experiências de catadores de materiais recicláveis de uma cooperativa de Goiânia-GO - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
Humans have significantly impacted the environment, mainly due to the capitalist production system, which is grounded on activities of subsistence and on the idea of improving life quality. Although it is important to support economic development, it is crucial to nurture social and environmental awareness based on balance and sustainability. As collaborators in this process of sustainability, there are the collectors of recyclable materials. This study has the aim to make these essential environmental collectors visible, who are, most importantly, workers seeking to provide for their families in spite of their work, which results in exclusion and social invisibility; and unveil the realities and experiences of these recyclable materials collectors at a recycling cooperative in Goiânia-GO, so that these important environmental agents be made apparent. In order to achieve it, the following specific objectives were considered: (i) understand the relation between sustainability, environment and environmental education, (ii) comprehend the relation between cooperativism and environmental sustainability, and (iii) understand the living conditions of recyclable materials collectors and the environmental potentiality of their actions. The methodology approached the phenomenological method, as the study focuses on the comprehension/interpretation of the participants’ realities and experiences; under a qualitative approach, in exploratory research regarding its goals, with bibliographic and empirical procedures. Narrative interviews were used for data collection. The results show the participants’ will power and capacity to overcome numerous daily adversities; they also show that the collectors’ actions towards sustainability contribute to decrease the solid sediments daily discarded by the population; they reveal that, among the collectors, there has been a history of informal employment, which is based on their necessity to prematurely contribute to the survival of their families, and that is worsened by the lack of fixed salaries, in addition to not having labor guarantees. It is necessary that these employees not only survive to their varied problems, but that they live with fundamental rights, but for this to happen, they must be made “visible”, not only to the eyes of society, but also to the government. Therefore, it is crucial to promote studies and strategies to ensure the indispensable improvements to achieve sustainability.
Environment and cooperativism: realities and experiences of recyclable material collectors from a recycling cooperative in Goiânia-GO
Keywords: Educação ambiental; Catadores de materiais recicláveis - Cooperativismo; Environmental education; Recyclable materials collectors - Cooperativism; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS SOCIAIS APLICADAS::ECONOMIA; CIENCIAS BIOLOGICAS::ECOLOGIA